2015
DOI: 10.1007/s00604-015-1566-9
|View full text |Cite
|
Sign up to set email alerts
|

Porous carbon derived from aluminum-based metal organic framework as a fiber coating for the solid-phase microextraction of polycyclic aromatic hydrocarbons from water and soil

Abstract: A nanoporous carbon derived from an aluminumbased metal-organic framework was deposited on stainless steel wires in a sol-gel matrix. The resulting fibers were applied to the solid-phase microextraction of the polycyclic aromatic hydrocarbons (PAHs) naphthalene, acenaphthene, fluorene, phenanthrene and anthracene from water and soil samples. The fiber was then directly inserted into the GC injector and the PAHs were quantified by GC-MS. The effects of salt addition, extraction temperature, extraction time, sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 38 publications
0
15
0
2
Order By: Relevance
“…Graphene [113,114], graphene oxide [115][116][117], MWCNTs [118,119] and other carbon based materials [120] have also been successfully employed as SPME sorbent coatings, either neat or combined with other materials in order to generate more efficient composites. These materials exhibit high chemical, thermal and mechanical stability, as well as great affinity towards PAHs.…”
Section: Solid-phase Microextraction Of Pahs From Environmental Matrimentioning
confidence: 99%
“…Graphene [113,114], graphene oxide [115][116][117], MWCNTs [118,119] and other carbon based materials [120] have also been successfully employed as SPME sorbent coatings, either neat or combined with other materials in order to generate more efficient composites. These materials exhibit high chemical, thermal and mechanical stability, as well as great affinity towards PAHs.…”
Section: Solid-phase Microextraction Of Pahs From Environmental Matrimentioning
confidence: 99%
“…Their application as SPME coating for soil analysis has been extensively investigated in recent years, both as regards the use of new structural variants and their synthesis. After their preparation, these SPME fibers were successfully used in the analysis of trace levels of fungicides [93], PAHs [19,[94][95][96], PCBs [97,98], polybrominated diphenyl ethers (PBDEs) [99].…”
Section: Soilmentioning
confidence: 99%
“…MOF coatings were also prepared by using 2-aminoterephthalic acid and Al salts and termed MIL-53 (Al). These MOFs were employed for the extraction of organochlorine pesticides [123] and PAHs [95]. Experimental results showed that the NH 2 -MIL-53(Al) SPME coating was solvent resistant and thermostable, and its efficiency for organochlorine pesticides was higher than that of commercially available SPME fiber coatings such as polydimethylsiloxane, polydimethylsiloxane-divinylbenzene, and polyacrylate.…”
Section: Drinking Watermentioning
confidence: 99%
“…The complex material was modified into SPME fibers to capture PAHs from environmental water samples. PAHs are highly carcinogenic and can damage the reproductive system, and this MOF‐based SPME method has been widely utilized for capturing these concerning compounds . The MON shells were hydrophobic, which enabled them to stably capture PAHs from water matrixes.…”
Section: Application Of Mofs For Sample Preparationmentioning
confidence: 99%